Subclinical disease among people with culture-confirmed pulmonary tuberculosis in Singapore - a retrospective study - Yi Rong Chew; Jun Yang Tay; Win Mar Kyaw; Po Ying Chia; Deborah Hee Ling Ng (International Journal of Infectious Diseases)
Objectives: Subclinical tuberculosis (TB) is challenging to diagnose due to the lack of a clear definition and symptoms. This study aimed to describe the subclinical disease spectrum among people with culture-confirmed pulmonary TB routinely diagnosed in Singapore, a country with moderate incidence, using different definitions. It also aimed to identify risk factors for subclinical TB and the current diagnostic approaches in detecting subclinical TB. Methods: A retrospective analysis of sputum culture-positive pulmonary TB cases reported to the Singapore National TB Registry from January 1, 2004 to December 31, 2023 was conducted. Two definitions for subclinical TB were used: sputum culture-positive TB with no cough or cough for less than 2 weeks for definition 1 and no cough for definition 2. Results: Of 18,693 pulmonary TB cases notified, 41.6% and 31.6% met the first and second definition of subclinical TB, respectively. However, neither definition performed better in detecting subclinical TB (receiver operating characteristics curve). The majority of cases (96.7% and 96.0% respectively) had abnormal chest X-ray findings, and a high proportion had smear-positive results (40.0% and 35.6%, respectively). Sputum TB polymerase chain reaction (PCR) was significant in picking up subclinical TB adjusted odds ratio 1.20 (95% confidence interval 1.10-31), although 42.2% with no persistent cough and 41.2% with no cough did not have sputum TB PCR tested, highlighting gaps in diagnostic practices. Together, older adults (aged ≥70 years) and immunocompromised individuals, including those with end-stage renal failure, steroid therapy, malignancy, and HIV, were more likely to have subclinical TB. Conclusions: Our study suggests that subclinical TB are more likely to occur in those older than 70 years and those with immunocompromising conditions. The use of diagnostics such as chest X-ray and sputum TB PCR are helpful in diagnosing subclinical TB. Further research is necessary to evaluate other screening tools in detecting these early disease states.